Nafkah Suami Miskin Persfektif Imam Abu Hanifah - Muhammad Al-Fayyad Rafiqi; Abu Hanifah (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
Maintenance is one of the important aspects of married life that is regulated in Islamic law. In this context, an understanding of the maintenance of poor husbands becomes very crucial, especially in the perspective of Imam Abu Hanifah. This study aims to examine Imam Abu Hanifah's view on the obligation of maintenance for husbands who are poor and its implications for the social and economic life of the family. This research methodology uses a qualitative approach with literature analysis from various sources, including fiqh books and scientific journals. The results show that even though the husband is poor, he still has the responsibility to provide maintenance according to his ability.